Does Economics Make You Sexist? - Valentina Paredes; M. Daniele Paserman; Francisco J. Pino (Institute of Labor Economics (IZA), 2020)
Recent research has highlighted unequal treatment for women in academic economics along several different dimensions: promotion, hiring, credit for co-authorship, and standards for publication in professional journals. Can the source of these differences lie in biases against women that are pervasive in the discipline, even among students in the earliest stages of their training? In this paper, we provide direct evidence on the importance of explicit and implicit biases against women among students in economics relative to other fields. We conducted a large scale survey among undergraduate students in Chilean universities, among both entering first-year students and students in years 2 and above. The survey elicits measures of implicit bias, explicit bias, and gender attitudes. We document that, on a wide battery of measures, economics students are more biased than students in other fields. There is some evidence that economics students are more biased already upon entry, before exposure to any economic classes. The gap becomes substantially more pronounced among students in years 2 and above, in particular for male students. We also find evidence of an increase in bias in a sample of students that we can follow longitudinally. Differences in political ideology and religiosity explain essentially all the gap at entry, but none of the increase in the gap with exposure. Exposure to female students and female professors attenuates some of the bias of economics students.
Keywords: J16; J71; A22; A13; A14; 330; discrimination; implicit biases; sociology of economics